(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
Technology has enhanced data exchange in real time thus improving cooperation between people in an innumerable variety of fields. Undoubtedly it had a great impact in creative writing, facilitating the massive growth of narrative community projects and the birth of new collective authors. These modifications of the traditional way of interrelating set the ground to question the identity problem from the double perspective of the critic and of the writer. In other artistic disciplines such as cinema and theatre this matter had already been faced in other terms. Who is the author of the film? Is it only the director or maybe are also the screen player, the producer and the actors involved? Similar questions, can be asked for what concerns the narrative of the collective authors. What is the birth process of a work when it is not elaborated by a single mind? How is it possible to evaluate a writing style if it is collective? Do intention and style belong to the collective author, to each member who forms it or to the work in its complexion as a new independent entity? An empirical approach to the practices of some of the most outstanding collective phenomena of the recent Italian narrative (we take into consideration case studies such as Wu Ming , Kai Zen, S.I.C.) may offer the challenging ground to investigations, not only theoretical, that may contribute to find answer to such a questions.